The influence of strong social ties on the choice of long-term care model for middle-aged and older adults in China - Jing, Tao; Zhao, Xinmeng; Xing, Huixia; Bao, Chuang; Zhan, Lanxi (Frontiers in Public Health, 2023)
With the acceleration of population aging in China, the care of middle-aged and elderly people has become the focus of social attention. As an "acquaintance society" in China, strong social relations play an important role in residents' access to information and resource allocation, which has an impact on the choice of long-term care model for middle-aged and elderly people. Based on the 2018 CHARLS data and Logistic binary model, this paper conducted an empirical analysis. The research showed that: Kinship and friendship in social relations will have a positive impact on middle-aged and elderly people's choice of social care model; The heterogeneity analysis showed that the strong social relationship significantly affected the choice behavior of long-term care model of residents in central and western China and rural areas. In this paper, the "SIRS infectious disease model" was further constructed to analyze the transmission mechanism of strong social ties. The results showed that residents who attach importance to strong social ties are more likely to incur medical transfer expenditure, thus further increasing their own demand for formal care model. The policy implication of this paper is to promote the coordinated development of long-term formal care and strong social relations, further promote the socialization of formal care model while relying on traditional family care, and build a multi-level and diversified long-term care system for middle-aged and elderly people.